The Inverse Precise Placement of Numbers Based at Pythagoras 1:3 and the Precise Configuration of Numbers as the Basis of a Unified Theorem That Binds the Physics of Mass, Space, Energy and the Torque Power (Inertia) That Sustains the Finite Universe. - Cameron, Vinoo (JOURNAL OF ADVANCES IN PHYSICS, 2019)
This paper is based on the precise inverse cone of Pythagoras 1:3. As in section 1 of this paper, all mathematics presented in this paper is by precise mathematics equations and the author has maintained by proof that the base numbers constant from which all physics constants can be derived are -1 to 19 ( the value 6 is as per this paper is the constant for expansion of all bounded space and 19 is the patent “end value” of the base constant numbers as shown in section 1 and referenced in this section11). Numbers as created and as placed at the cone of Pythagoras 1:3 are precise manifestation of the numbers of linear composite. However, this paper shows that the invention of designated angles (Trigonometry) is an approximate arbitrary arrangement invented by man, based on the created fixed angle of 90 degrees and is certainly flawed as shown here in this paper. Likewise, any attempts to measure curvature by linear numbers is fraught with much error. The author maintains that “If the atomic density and structure of meteorites from far space have the same configuration as those found on this earth, then by all created logic , these numbers configuration presented in these two papers and the book (The God of Papa Einstein and Sir Isaac Newton) are a constant unified theorem of all the space and mass ( Quantum mechanics) in the universe”. Einstein’s Theory of relativity and all other interstellar phenomena are not addressed in the context of this paper because all this is observed science phenomena and not a physical science, and this paper deals with precise numbers configuration as in the section 1 of the paper. Einstein’s relativity is a real observed natural phenomenon, not science by itself, it is a natural aberration of the fact that observed relativity is due to inherent curvature and linear relationship between any two points in the universe and because of the spiral progression of curved space. Neither does light bend it appears to bend, nor does time really dilate in real terms even though it is a real observed phenomenon, neither numbers or distances dilate by any continuum, unfortunately, that is why Einstein’s misconception about time dilation is a Theory and will always be Theory.